Voltammetric analysis of weak acids with microelectrodes - Canhoto, Carla (2004)
The role of H+ on the steady-state voltammetric limiting current (IL) of weak acids (HA) reduction was studied considering results from either lactic acid or acetic acid solutions at constant pH. For solutions with pH > pKa or pH near pKa the [H+] effect on the IL vs cHA slope was important even when the H+ current contribution was minor. In opposition, when pH << pKa high H+ current contributions were found nevertheless the IL vs cHA slope was almost insensitive to pH. A general relationship between IL and cHA was derived considering both the H+ current contribution and the dissociation extent. This equation allows the analytical determination of weak acids, alone or in the presence of strong acids, from experimental IL and pH. Acids identification can also be performed through the presented expression, following the IL susceptibility to pH at constant cHA.